Novel therapeutic modulators of astrocytes for hydrocephalus - Yang, Yijian; Wang, Chuansen; Chen, Rui; Wang, Yuchang; Tan, Changwu; Liu, Jingping; Zhang, Qinghua; Xiao, Gelei (Frontiers in Molecular Neuroscience, 2022)
Hydrocephalus is mainly characterized by excessive production or impaired absorption of cerebrospinal fluid that causes ventricular dilation and intracranial hypertension. Astrocytes are the key response cells to inflammation in the central nervous system. In hydrocephalus, astrocytes are activated and show dual characteristics depending on the period of development of the disease. They can suppress the disease in the early stage and may aggravate it in the late stage. More evidence suggests that therapeutics targeting astrocytes may be promising for hydrocephalus. In this review, based on previous studies, we summarize different forms of hydrocephalus-induced astrocyte reactivity and the corresponding function of these responses in hydrocephalus. We also discuss the therapeutic effects of astrocyte regulation on hydrocephalus in experimental studies.